2013
DOI: 10.1016/j.joca.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Statistical shape modeling of proximal femoral shape deformities in Legg–Calvé–Perthes disease and slipped capital femoral epiphysis

Abstract: Introduction The current understanding of morphological deformities of the hip such as femoroacetabular impingement (FAI), Legg-Calve-Perthes disease (LCPD), and slipped capital femoral epiphysis (SCFE) is based on 2-dimensional metrics, primarily involving the femoral head, that only partially describe the complex skeletal morphology. Objective This study aimed to improve the 3-dimensional understanding of shape variations during normal growth, and in LCPD and SCFE, through statistical shape modeling. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Previous statistical shape models investigating morphological variation in bones have shown that size dominates the first principal component (Chan et al, 2013; Cootes et al, 1992; Fitzpatrick et al, 2011; Zhang et al, 2014). This was the case in our statistical shape model, where the first principal component accounted for 71% of the morphological variation in CMC joint bones, which was attributed to size (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous statistical shape models investigating morphological variation in bones have shown that size dominates the first principal component (Chan et al, 2013; Cootes et al, 1992; Fitzpatrick et al, 2011; Zhang et al, 2014). This was the case in our statistical shape model, where the first principal component accounted for 71% of the morphological variation in CMC joint bones, which was attributed to size (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…For statistical shape models involved in biological systems, size typically dominates the first principal component (Chan et al, 2013; Cootes et al, 1992; Fitzpatrick et al, 2011; Zhang et al, 2014). To investigate pure-shape differences in the trapezia and 1 st metacarpal bones between men and women, a general Procrustes analysis (least-squares minimization of correspondent point differences) was performed on the fitted meshes to filter out scaling variations (Bischoff et al, 2013; Ross, 2004; Stegmann and Gomez, 2002) producing the size-normalized shape model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While 3D bone shape analysis using MRI has the potential to extract more detailed shape features, challenges such as segmenting the bone and other tissues becomes time intensive if done manually, or even semi-automatically [2831]. Despite this constraint Three-dimensional Statistical Shape Modeling (SSM) has been increasingly employed in studies involving knee and hip OA [2832]. …”
Section: Introductionmentioning
confidence: 99%
“…Previously, the authors conducted a study in which a SSM model was created for asymptomatic, LCPD, and SCFE patients. That study showed that statistical shape parameters described coordinated, regional shape deformations that correlated with certain traditional 2-D measurements 26 . One limitation of previous studies is that modes of variation can be difficult to interpret and apply in a clinical setting.…”
Section: Introductionmentioning
confidence: 84%